Patient Safety Threats in Information Management Using Health Information Technology in Ambulatory Cancer Care: An Exploratory, Prospective Study. Issue 8 (December 2021) - Pfeiffer, Yvonne; Zimmermann, Chantal; Schwappach, David L. B.
Abstract : Background: Cancer care is complex, involving highly toxic drugs, critically ill patients, and various different care providers. Because it is important for clinicians to have the latest and complete information about the patient available, this study focused on patient safety issues in information management developing from health information technology (HIT) use in oncology ambulatory infusion centers. Objective: The aim was to exploratively and prospectively assess patient safety risks from an expert perspective: instead of retrospectively analyzing safety events, we assessed the information management hazards inherent to the daily work processes; instead of asking healthcare workers at the front line, we used them as information sources to construct our patient safety expert view on the hazards. Methods: The work processes of clinicians in three ambulatory infusion centers were assessed and evaluated based on interviews and observations with a nurse and a physician of each unit. The 125 identified patient safety issues were described and sorted into thematic groups. Results: A broad range of patient safety issues was identified, such as data fragmentation, or information islands, meaning that patient data are stored across different cases or software and that different professional groups do not use the same set of information. Conclusions: The current design and implementation of HIT systems do not support adequate information management: clinicians needed to play very close attention and improvise to avoid errors in using HIT and treat cancer patients safely. It is important to take the clinical front-end practice into account when evaluating or planning further HIT improvements.